Self-Cleansing Urban Drain Using Sediment Flushing Gate Based On Incipient Motion - Charles, Bong Hin Joo (2013)
Sediment deposition in urban open concrete storm drain has caused many adverse effects to the drainage system such as flash flood and environmental pollution. This study aimed to provide recommendations for the purpose of sedimentation mitigation in urban open concrete storm drain. To understand the physical characteristics of sediment deposition; sampling was taken from 57 locations in Kuching city, surrounding towns outside Kuching city and Penang consisting of residential, commercial and industrial areas and subjected to sieve analysis. Results showed that the samples were mainly inorganic and noncohesive with sand as the major component followed by gravel and silt and clay for most of the samples. To improve the design criteria, incipient motion experiments were conducted in a 0.6 m wide flume for sediment with 50 d sizes of 0.81 mm, 1.53 mm 4.78 mm. Combining the results from the current incipient motion experiments with the results from an earlier researcher for a 0.3 m wide flume, multiple linear regression were performed and the best equations for each of the critical shear stress and critical velocity approach were developed. A design chart relating the self-cleansing design relationship between drain minimum slope with the design minimum flow rate and the respective standard drain size was also developed. To further improve the self-cleansing capability of open concrete storm drain, a tipping flush gate was designed and installed on site at Taman Pekaka, Nibong Tebal, Penang and subjected to monitoring for four months between 14th November 2012 and 15th March 2013.